Peran Pondok Pesantren dalam Mencetak Jiwa Entrepreneurship (Studi di PP. Darul Muslim Tulung Balak Lampung Timur) - Siti Khusnul Mahfudzoh; Ikhwan Aziz Q; Rina Mida Hayati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Islamic boarding schools as one of the oldest educational institutions in Indonesia have an important role in introducing entrepreneurship to students. To grow and develop an entrepreneurial spirit and create entrepreneurs, of course we need certain parties, whether government or private or individuals. Entrepreneurial development through instilling an entrepreneurial attitude or mentality, namely with an attitude of independence, honesty, and discipline. And entrepreneurial development through skills. The role of the Darul Muslim Tulung Balak Islamic boarding school in creating an entrepreneurial spirit, namely Dare to take risks, is carried out by implementing business management consisting of planning, organizing, preparing personnel, directing, and supervising. Being innovative is carried out by forming an entrepreneurship program in the form of agricultural and fishery businesses. Being proactive is carried out by dividing tasks to each student, as well as giving punishment in the form of sanctions if students are not proactive in carrying out all their obligations. Pondok Pesantren Darul Muslim has carried out its function as an institution that provides entrepreneurship education which is carried out in two ways, namely: cultivating an entrepreneurial spirit and developing entrepreneurship through skills. In this case, the role of the Darul Muslim Islamic Boarding School is to provide teaching by providing material and theory in developing the soft skills of students and female students. And this learning is not only carried out in theory and material, but students or students and supervisors jointly apply the theory that has been obtained before in field practice.